ACUTE EFFECTS OF DIFFERENT INTENSITIES RESISTANCE TRAINING ON INFLAMMATORY MARKERS OF WOMEN WITH SEVERE OBESITY - Thaurus Vinícius de Oliveira Cavalcanti; Luís Felipe de Almeida Diniz; Bárbara Amaral Bruno Silva; José Cristiano Faustino dos Santos; Luiz Fernando de Lima; Madi Veiga Diniz; Virgínia Maria Barros de Lorena; Paulo Roberto Cavalcanti Carvalho (Journal of Physical Education)
ABSTRACT This study objective to compare the acute effects between one resistance training bout with high versus moderate intensities on inflammatory markers in women with severe obesity. Experimental crossover study, performed with adult women with severe obesity (BMI ≥ 40.0 kg/m²; age ≥ 18 years old). Each participant performed a high and moderate intensity resistance training (HIRT and MIRT, respectively) with an interval of 7 days between bouts. Four exercises were performed in the both protocols, with total training volume equalized. MIRT consisted of 3 sets of 8 repetitions each, with an intensity of 75% of 1RM, while HIRT consisted of 2 sets of 6 repetitions, followed by a 20-second rest, with a new performance of 2 to 3 repetitions, with one more rest of 20s and finishing with 2 to 3 more repetitions, at an intensity of 85% of 1RM. Blood samples were collected before, 15 minutes after and 24 hours after both training protocols. The inflammatory markers analyzed were IL-2, IL-4, IL-6, IL-10, TNF-α and IFN-γ. Nine participants have completed the intervention (n=9; 35.2 ± 10.93 years old; BMI = 48.3 ± 5.06 kg/m²). The Mann-Whitney U test showed that there was no significant difference between the HIRT and MIRT in the concentration of markers. Friedman's test did not report significant differences between intragroup measures for the HIRT as well as MIRT. This research suggests that a single session of high or moderate intensity resistance training does not change the inflammatory status of women with severe obesity.